EMILY TEETER (ed.), Before the Pyramids. The Origins of Egyptian Civilization. Oriental Institute Museum Publications 33. Chicago, Oriental Institute of the University of Chicago, 2011. 288 pp. ISBN 978–1–885923– 82–0. U$D 39,95 - Tamorri, Verónica (2012)
Fil: Tamorri, Verónica. Durham University; Inglaterra